Cushing Syndrome pada Anak Perempuan 5 Tahun: Sebuah Laporan Kasus - Muhammad Yazid Daradjat; Ismi Citra Ismail (Medula, 2026)
Cushing’s syndrome (CS) is a rare multisystem endocrine disorder characterized by excessive glucocorticoid levels. In children, this condition is uncommon, with a reported global incidence of approximately 1:5,000,000–10,000,000 per year, and may result from endogenous overproduction or prolonged irrational use of exogenous steroids. This case report describes a 5-year-6-month-old girl presenting with fever accompanied by nausea, vomiting, and diarrhea. The patient had a history of recurrent unexplained fever for the past two years and had been repeatedly treated with paracetamol and dexamethasone without medical consultation until symptoms improved. The diagnosis was supported by physical examination findings suggestive of obesity, diastolic blood pressure above the 95th percentile, moon face, buffalo hump, acanthosis nigricans, and abdominal striae. Supporting examinations revealed adrenal ultrasonography within normal limits. Management included gradual tapering off dexamethasone and close observation for signs of adrenal crisis, followed by planned evaluation of cortisol and plasma adrenocorticotropic hormone levels. Long-term use of steroid medications without proper medical supervision remains the most common cause of CS in pediatric patients. This report emphasizes the importance of stricter regulation of over-the-counter steroid distribution by relevant stakeholders and highlights the critical role of clinicians in educating parents regarding the appropriate use of steroid medications to prevent the development of Cushing’s syndrome in children.